Extended spectrum Beta lactamases in Gram negative bacilli: characterization and prevalence by type of infection. Systematic Review - Loor-Moreira, Jocelyn; Parraga-Roca, Cristina; Lucas Párrales, Elsa Noralma (Kasmera, 2021)
Gram-negative bacilli that produce extended-spectrum β-lactamases are pathogens that represent a problem, due to the scarce alternative treatment and the various infections they cause, highlighting the situation with high epidemiological interest, due to the increasing prevalence. The objective of this review was to assess extended spectrum beta-lactamases in Gram-negative bacilli, their characterization and prevalence by type of infection. Medline, PubMed, SciELO, Free Medical Journals, Cochrane Library and academic Google databases were searched for the last 3 years of publication, including articles in Spanish and English and 104 articles were analyzed. ESBL-producing gram-negative infections include: urinary tract, gastrointestinal, intra-abdominal, nosocomial, bloodstream infections, pneumonia, and meningitis. The phenotypic characteristics of ESBL mainly comprise the enzymes CTX-M, TEM and SHV. In Latin America, the prevalence of Escherichia coli producing ESBL has exceeded 30%. The resistance given by ESBL, especially by Gram-negative ones, are the result of the presence of class A enzymes that promote various infections, generating a problem for medical personnel when suggesting a treatment, due to the consequences that this could generate in the future